Histopathological Description of Invasive Breast Carcinoma Patients at Dr.M.Djamil Hospital 2019-2020 - Azzahra Saidah Ramadhani; Yenita; Yaunin, Yaslinda (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: Breast carcinoma is a type of malignancy originating from the epithelium cells of the breast. There are several risk factors that are often associated with this disease, such as : genetics, age, gender, obesity, hormonal, etc. The aim of this study is to describe the histopathological description of invasive breast carcinoma patients based on age and body mass index at Dr. M. Djamil Padang hospital in 2019-2020. Methods: This research is descriptive observational using secondary data from the results of histopathological examination and medical records in May 2022-June 2022. The data were analyzed using univariate analysis. Results: The results showed that the majority of patients were in the group of age between 46 to 55 years old (33.1%), obesity (33.8%), Invasive Carcinoma of No Special Type (54, 9%), and grade III (69%). Most patients with Invasive Carcinoma of No Special Type are in the group of age between 46 to 55 years old (28,2%) with obesity (35,9%). Patients with grade III mostly in the group of age between 46 to 55 years old (39,8%) with obesity (35,7%). Conclusion: The conclusion of this study is that the majority of invasive breast carcinoma patients are Invasive Carcinoma of No Special Type, grade III, in the group of age between 46 to 55 years old age, with obesity